أثر نظام تحميل الذرة السكرية على البطاطا الخريفية في الإنتاجية ومعدل استغلال الأرض - بوراس, متيادي; رقية, نزيه; الببيلي, روعة (Latakia University Journal -Biological Sciences Series, 2018)
نفذ البحث في الموسمين الزراعيين المتتاليين 2003 و2004 في مركز البحوث العلمية الزراعية بحمص لدراسة أثر تحميل الذرة السكرية "صنف الفيحاء" على البطاطا "صنف سبونتا" في الإنتاجية ومعدل استغلال الأرض.شملت الدراسة ستة معاملات لمقارنة أبعاد زراعية مختلفة من التحميل مع الزراعة المفردة وهي: 1- البطاطا (ب). 2- الذرة السكرية (ذ). 3- بطاطا +ذرة في نفس الخط (بأبعاد 30 سم لكل منهما). 4- بطاطا +ذرة في نفس الخط (بأبعاد 30 سم للبطاطا و45 سم للذرة). 5- بطاطا +ذرة في نفس الخط (بأبعاد 30 سم للبطاطا و60 سم للذرة). 6- بطاطا +ذرة في نفس الخط (بأبعاد 30 سم لكل منهما). زرعت الذرة بعد 15 يوماً من زراعة البطاطا. جرت زراعة كل معاملة في ثلاثة خطوط طول الخط 3.9 م تبعد عن بعضها 75 سم ضمن قطعة تجريبية مساحتها 6.8 م2 وبأربعة مكررات للمعاملة الواحدة. اعتمد تصميم القطاعات العشوائية البسيطة في توزيع المعاملات. أظهرت النتائج أن إجمالي إنتاجية وحدة المساحة في نظام الزراعة التحميلية كان أعلى من إنتاجية كل محصول منفرداً مع تفوق المعاملة الخامسة(ب30+ذ60 سم)على باقي معاملات التحميل. فقد بلغ متوسط إنتاجية وحدة المساحة فيها 34.7 طن/هـ في حين تراوح في بقية المعاملات (التحميل)من 26.3-30 طن/هـ. وبالمقابل انخفضت إنتاجية كلا المحصولين في نظام الزراعة التحميلية بنسبة تراوحت بين 16-56% في محصول البطاطا وبين7-28 % في محصول الذرة مقارنة مع إنتاجية كل محصول منفرداً. كما أظهرت النتائج ازدياد قيمة معدل استغلال الأرض LER (Ratio Land Equivalent)عند تطبيق نظام الزراعة التحميلية بالمقارنة مع الزراعة المنفردة حيث تراوحت قيمته بين 1.31-1.56 في نظام التحميل مقابل 1 في الزراعة المنفردة. The research was conducted in successive agricultural seasons 2003-2004 at Homs Research Center. This research aimed to study the effect of Sweet corn "cv. Alfaiha” intercropping on Autumn Potato “cv. Spunta” in terms of productivity and land equivalent ratio (LER). The study included /6/ treatments to compare different planting distances of intercropping with single farming. These treatments were: Potato. Sweet corn. Potato + corn in the same row (30 cm for each). Potato + corn in the same row (30 cm for potato & 45 for corn). Potato + corn in the same row (30 cm for potato & 60 for corn). Potato + corn in the same row (30 cm for each). Corn was planted /15/ days post potato plantation. Each treatment was planted in 4 replications. Each replication consisted of a plot (6.8m2) with 3 rows, of 3.9 m length and an inter-rows distance of 75cm. The experimental design was completely randomized design. Results showed that the total productivity per area unit in intercropping farming was higher than it was with just one crop. Treatment (No.5) was superior to the other intercropping treatments. In this treatment, productivity average reached 34.7 t/ha, while the other treatments were between 26.3-30 t/ha. On the other hand, the productivity of both crops in intercropping farming decreased by 16-56% for potato, and 7-28% for maize in comparison with the productivity of each crop alone. The results showed that LER was increased when intercropping system was applied comparing to single agriculture. LER ranged from 1.31 to 1.56 for intercropping against 1 in single cultivation.